Masjid Raya Datuk Badiuzzaman Surbakti: Sejarah dan Arsitekturnya - Khoiriyah, Fitri; Naldo, Jufri; Azhar, Anang Anas (Warisan: Journal of History and Cultural Heritage, 2023)
This article aims to reveal the history and architecture of Masjid Agung Datuk Badiuzzaman Surbakti. This research adopts a qualitative research design with a descriptive approach and employs historical methods in the data collection and analysis process. There are four stages conducted in this research, namely heuristic, verification, interpretation, and historiography. Data were obtained through interviews, observations, and documentation. The research findings indicate that Masjid Agung Datuk Badiuzzaman was established in 1885 AD by Datuk Badiuzzaman Surbakti, the eighth king of the Sunggal Kingdom, also known as the King of Serbanyaman. Furthermore, the study also demonstrates that until the present day, the mosque stands firmly as a symbol of history and the community's beliefs. The architecture of this mosque reflects the beauty of past architectural art, which combines traditional and spiritual values within its structure. This research provides a significant contribution in understanding the role of Masjid Agung Datuk Badiuzzaman Surbakti in the context of local history and architecture, enriching insights into the cultural and religious heritage of this region.